1963
DOI: 10.1002/jlac.19636700103
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorallen als Zwischenstufe der Dehydrochlorierung von 3‐H‐Pentachlorpropen‐(1) zu Perchlor‐1.2‐dimethylen‐cyclobutan

Abstract: Die Dehydrochlorierung von 3-H-Pentachlorpropen-(l) (I) mit NaNH2 in flus-sigem NH3 + Propan bei -75" fuhrt zu dem sehr reaktionsfahigen Perchlorallen (11), das uberaus leicht zu Perchlor-1.2-dimethylen-cyclobutan (V) dimerisiert. Das Dimere laBt sich zu Perchlor-3.4-dimethylen-cyclobuten-(l) (XII) dechlorieren und in eineperchlorierte Mono-bzw. Dicarbonsaure uberfuhren, deren katalytische Hydrierung zu bekannten Cyclobutancarbonsauren neben IR-und RAMAN-spektroskopischen Befunden fur die Konstitution beweisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…After complete consumption of the starting material (monitored by GC), the reaction mixture was cooled to room temperature (r. t.), and the organic phase was separated. The inorganic phase was extracted twice with chloroform ( HMC 500 C to give pure nitroethene 2 (78.0 g, 33%, bp 56-57 °C/25 mbar), chloropicrin (7) (2.9 g, 1.3%, bp 39-40 °C/25 mbar, bp 110-111 °C/988 mbar [26] ) and nitroethane 8 (23.9 g, 8.4%, bp 65-66 °C/25 mbar, bp 63 °C/11 mbar [18] ).…”
Section: Nitration Of Trichloroethenementioning
confidence: 99%
See 1 more Smart Citation
“…After complete consumption of the starting material (monitored by GC), the reaction mixture was cooled to room temperature (r. t.), and the organic phase was separated. The inorganic phase was extracted twice with chloroform ( HMC 500 C to give pure nitroethene 2 (78.0 g, 33%, bp 56-57 °C/25 mbar), chloropicrin (7) (2.9 g, 1.3%, bp 39-40 °C/25 mbar, bp 110-111 °C/988 mbar [26] ) and nitroethane 8 (23.9 g, 8.4%, bp 65-66 °C/25 mbar, bp 63 °C/11 mbar [18] ).…”
Section: Nitration Of Trichloroethenementioning
confidence: 99%
“…85-87 °C. IR (KBr): ν = 2998, 1686, 1583, 1562, 1497, 1443, 1394, 1329, 1251, 1101, 1048, 998, 953, 800, 756, 692 cm 2948, 2834, 1690, 1592, 1556, 1453, 1400, 1334, 1315, 1219, 1148, 1118, 1015, 956, 869, 807, 731, 692, 632 cm 2936, 1675, 1591, 1558, 1447, 1401, 1357, 1332, 1285, 1204, 1092, 1007, 969, 892, 809, 758, 683, 621 cm 3396, 1640, 1585, 1531, 1487, 1432, 1362, 1298, 1233, 1133, 1119, 1011, 930, 826, 713, 661, 539 cm (26). To a suspension of oxime 19 (352 mg, 1.00 mmol) in 5 mL of MeOH at 0 °C was added dropwise 1 mL (10 mmol) of conc.…”
Section: 1-bis(azocan-1-yl)-2-chloro-2-nitroethene (13) Was Preparementioning
confidence: 99%
“…It shows that these reactions are regio-and stereospecific and that a cis-l,2-disubstituted double bond reacts faster than the ,NMe 2 BF 4 e Η Me trans isomer. Halogenated alienes are also potent dienophiles (Knoth and Coffman, 1960;Roedig et al, 1963) as shown, for instance, by the formation of a cycloadduct from tetrachloroallene and cyclopentadiene at 263°K. The behavior of tetramethylketeniminium salts toward cis-fixed dienes is totally different from that observed with ketenes.…”
Section: Reactions With Dienesmentioning
confidence: 99%
“…For the synthesis of perchloroalkenes, see: Prins (1949); Roedig et al (1963). For structures of perchloroalkenes, see: Herbstein (1979); Rao & Livingston (1958); Hopf et al (1991); Detert et al (2009).…”
Section: Related Literaturementioning
confidence: 99%